Government Communication and Public Participation in the Policy-Making Process in Indonesia: The Role of Constitutional Dialogue in Strengthening Democratic Legitimacy and Policy Accountability - Irmanjaya Thaher (International Research of Multidisciplinary Analysis, 2026)
Objective: This study aims to analyze the role of government communication and public participation in the policy-making process in Indonesia, with a focus on the contribution of constitutional dialogue to strengthening democratic legitimacy and policy accountability. Methods: This study employs a qualitative approach using a case study design, involving an in-depth analysis of policy documents, government digital communication platforms, and relevant academic literature. Data were analyzed thematically to identify communication patterns, participation mechanisms, and practices of constitutional dialogue. Results: Findings indicate that while there has been a significant increase in transparency and the use of digital technology for public participation, its implementation remains procedural in nature and is not yet fully deliberative. Public participation is often dominated by groups with better digital access, creating inequities in the deliberative process. Constitutional dialogue, although present in some policy initiatives, has not been strongly institutionalized and often does not result in substantive change. Conclusion: This study concludes that constitutional dialogue offers a potential normative framework for bridging the gap between government communication and public participation, but requires institutional strengthening and governance reforms to enhance democratic legitimacy and policy accountability in Indonesia effectively